Is asking only one member of a couple sufficient to determine who influences tourism decisions? - Rojas-de-Gracia, María Mercedes; Alarcón-Urbistondo, María del Pilar; Casado-Molina, Ana María (Elsevier, 2019)
Research on consumer behavior has placed considerable importance on identifying which member of a couple makes purchase decisions. However, numerous studies have relied solely on the response of one member, assuming that both are sufficiently in agreement, despite the lack of any clear support for this assumption of dyadic consensus. The aim of this study is to elucidate this question in tourism decisions, using a larger contemporary sample than those employed in other major studies. A further novelty of the study was to determine whether agreement could have been due to chance. Evidence was found of differences in the perception that each member of a couple had of the influence exerted. However, the degree of discrepancy between them depended on the aspect considered. The theoretical and practical implications of these findings are then discussed. -La investigación sobre el comportamiento del consumidor ha otorgado una importancia considerable a la identificación del miembro de la pareja que toma las decisiones de compra. Sin embargo, numerosos estudios se han basado únicamente en la respuesta de uno de los miembros, asumiendo que ambos están suficientemente de acuerdo, a pesar de la falta de un apoyo claro a esta hipótesis de consenso diádico. El objetivo de este estudio es dilucidar esta cuestión en las decisiones turísticas, utilizando una muestra contemporánea más amplia que las empleadas en otros estudios importantes. Otra novedad del estudio fue determinar si el acuerdo podría deberse al azar. Se encontraron evidencias de diferencias en la percepción que cada miembro de la pareja tenía de la influencia ejercida. Sin embargo, el grado de discrepancia entre ellos dependía del aspecto considerado. A continuación, se discuten las implicaciones teóricas y prácticas de estos hallazgos.
Keywords: Turismo - Toma de decisión; Consenso diádico; Acuerdo de respuesta; Roles de pareja; Toma de decisiones vacaciones familiares; Influencia percibida de la pareja; Dyadic consensus; Response agreement; Perceived partner influence; Family decision-making; Vacations; Couple roles